Factors influencing HPV vaccine acceptance among females in mainland China: a systematic review - Dapari, Rahmat; Li, Mengfan; Chen, XiJuan; Cui, Jinqi; Ahmad Zamzuri, Mohd ‘Ammar Ihsan; Hassan, Mohd Rohaizat; Che Dom, Nazri; Syed Abdul Rahim, Syed Sharizman (Elsevier B.V., 2024)
2015, 30,500 fatalities and 98,900 new cases of cervical cancer were reported. By 2030, the number of deaths from cervical cancer will grow by over 50%. China has been strengthening its cervical cancer prevention and treatment service system and enhancing the country’s comprehensive prevention and treatment capacity including HPV vaccination. Objective: A systematic review was conducted to examine and describe factors influencing HPV vaccine acceptance among females in mainland China. Method: A systematic search of Web of Science, PubMed, Scopus, EBSCOhost, and China National Knowledge Infrastructure (CNKI) was carried out from January 2000 to April 2023 for articles related to factors influencing HPV vaccine acceptability among females in mainland China. Result: Articles were screened by inclusion and exclusion criteria, and those that met the inclusion criteria were included in the study. Of the 10 included studies, the subjects involved university students, secondary school students, mothers, health professional students, medical professionals, and females. A review of the included studies revealed that there was a low level of acceptance of the HPV vaccine among women in mainland China as a whole. Factors influencing this acceptance included knowledge of the HPV vaccine, hearing about it, family history of infection-related diseases, cost, hearing about HPV/HPV vaccine/cervical cancer, vaccine safety, sex life, and sex education. Conclusion: Awareness of the HPV vaccine among females in mainland China is low, and this leads to a lack of acceptance of the HPV vaccine among females. The HPV vaccination program will benefit more from targeted HPV vaccine promotion campaigns based on factors influencing females’ acceptance of the vaccine, such as those conducted through the media, hospital publicity, and community publicity to increase women’s knowledge of the vaccine and improve vaccine acceptance.